(untitled) (TEST Ticontre. Theory Text Translation, 2020)
Literary and artistic Japanese culture enters Russian society at the end of the 19th century, thanks to the translation practices that have always been at the core of Russian Symbolism, which developed as an imitation of the analogous French movement, taking its shape from the Russian translations of Baudelaire, Rimbaud, and Verlaine and later widened its horizons appropriating also exotic literary models. The knowledge of exotic literatures brought about a widening of metrical forms used by Symbolist writers in their original works, among which the Japanese forms of haiku and tanka stand out. These forms, however, are always hybridised with symbols of Russianness, achieved through the use of the rhyme and the homologation technique. The article aims to highlight, within the Russian symbolist movement, the phenomenon of hybridisation of poetry with forms that are traditionally adopted by Japanese culture. The thesis is that the reception of poetic Japanese forms was marked by a conscious mediation with elements that were culturally understood as native, in a search for a voluntary hybridisation of the Self with the Other. Works by Valery Briusov, Konstantin Balmont and Andrei Bely will be analysed, and in the conclusions we will briefly discuss the coeval experimentations of exotic forms within visual art and music.